A Clinical Audit of Endoscopic Retrograde Cholangiopancreaticogram of Patients performed in a Secondary Care Hospital - Imran Anwar Khan , Sheikh Muhammad Mahmoud , Saman Saeed , Shajeel Akhtar , Muzammil Kataria , Imran Anwar Khan , Sheikh Muhammad Mahmoud , Saman Saeed , Shajeel Akhtar , Muzammil Kataria (Journal of Rawalpindi Medical College, 2020)
Introduction: Recent advances in ERCP techniques are developed to improve its efficacy and safety but there are limited data regarding the efficacy and safety of ERCP carried out in secondary care hospital setting using modern techniques. Objective: To perform a clinical audit of ERCP of patients performed in secondary care hospital. Materials and Methods: Cross-sectional study conducted at the Department of Gastroenterology hospital, Lahore from Jan 2018 - Dec 2018. After approval from the ethical committee and informed consent from subjects, detailed demographic information was collected and entered into a structured questionnaire. A total of 66 ERCP were included in the study by non-probability consecutive sampling. Data was analyzed in SPSS ver: 21.0. Frequency and percentages were calculated for qualitative variables like gender and diagnosis and complications. Results: A total of 66 ERCP were performed. The mean age of patients was 57.35 + 12.30. 36.4% were male and 63.6% were female in our study. 53.0% had malignant ERCP findings and 47.0% had benign pathology. Among malignant conditions were proximal CBD malignant strictures (25.8%), distal CBD stricture with ampullary growth (9.0%), distal malignant CBD stricture (6.0%), long distal malignant CBD stricture (9.0%), and complete malignant obstruction mid CBD (3.1%). Conclusion: The ERCP services provided at secondary care hospital are standardized with a desirable outcome. The rate of its technical success is comparable to tertiary care setting and complication rates are low alone with mortality related to the procedure.